(untitled) (Research, Society and Development, 2021)
This research aimed to identify previous knowledge and evaluate the knowledge built considering the participation in educational groups on breastfeeding, as well as to analyze the interactions, between professionals and pregnant women, that allow the construction of this knowledge from the groups. The method proposed was diagnostic, procedural and summative evaluation research and implemented with 90 pregnant women participating in an educational group at a Human Milk Bank, in Rio de Janeiro. The results analyzed shows that pregnant women built knowledge (51.1%), some maintained knowledge they already had (36.6%) and some women (12.2%) deconstructed the knowledge. The complexity of the theme and the gaps present guided the discussion. As final considerations, the authors propose the strategy of moving from banking to constructivist education, prioritizing a simplified and elementary information, allowing the treatment of these issues, as they are demand.